2018
DOI: 10.3390/w10050644
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of a Surface Flow Constructed Wetland Treating Agricultural Drainage Water in Northern Italy

Abstract: Agricultural drainage water that has seeped into tile drainage systems can cause nitrogen and phosphorus pollution of the surface water bodies. Constructed wetlands (CWs) can help mitigate the effects of agricultural non-point sources of pollution and remove different pollutants from tile drainage water. In this study, hydrological and water quality data of a Northern Italian CW that has been treating agricultural drainage water since 2000 were considered to assess its ability to mitigate nitrogen and phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Constructed wetlands are vegetated aquatic systems that can be adopted for the treatment of wastewater and agricultural drainage water (Lavrnic et al, 2018). Their ability to reduce ARGs in swine wastewater resulted in a 0.18-3 log decrease (He et al, 2020).…”
Section: Manure Treatmentsmentioning
confidence: 99%
“…Constructed wetlands are vegetated aquatic systems that can be adopted for the treatment of wastewater and agricultural drainage water (Lavrnic et al, 2018). Their ability to reduce ARGs in swine wastewater resulted in a 0.18-3 log decrease (He et al, 2020).…”
Section: Manure Treatmentsmentioning
confidence: 99%
“…This created the conditions for an extended residence time in the SFCW basin. Lavrnić et al [35] reported a similar situation in a study conducted on an SFCW in a nearby Italian region with similar climatic conditions: the authors found significant differences between inflow and outflow N concentrations when the residence time was longer, due to higher infiltration and nutrient losses, and increased pollutant removal. In 2009-2010, NO 3 -N inflow concentrations started to increase.…”
Section: Seasonal Trend Of N and P Flow-weighted Monthly Concentrationsmentioning
confidence: 58%
“…The HRT (Equation 3), also depicted below as nominal HRT (Equation (4))-commonly used by the authors-quantifies the contact time of the drainage discharge with the SFCW and is a key factor regulating P retention [76,92]. The P retention mechanisms present different requirements in terms of HRT for proper retention.…”
Section: Countrymentioning
confidence: 99%